Comparisons of sexual behaviors and STD prevalence among older and younger individuals with HIV infection - Önen, Nur F. (2010)
This study was developed to evaluate differences in sexual behaviors and incident bacterial sexually transmitted diseases (STDs) between older HIV-infected individuals and their middle-aged and younger counterparts. We conducted a prospective cohort study of HIV-infected individuals ≥ 18 years who had completed an annual standard of care assessment. Analyses were performed to examine differences in sexual behaviors and incident STDs between age groups: (30%) were 18–35 years (younger), (46%) were 36–49 years (middle-aged) and (24%) were ≥ 50 years (older). 541 individuals completed the assessment. Older individuals were most likely to be male and Caucasian with longest time since HIV diagnosis, greatest receipt of HAART and highest rates of HIV RNA < 50 copies/mL (all p<0.001). Reports of recent sexual activity decreased with age, (56% younger vs. 43% middle-aged vs. 27% older) (p<0.001), the median number of sex partners was 1 (range 1–25) and 68% overall reported using condoms consistently. The number of sexual partners and consistency of condom use did not differ by age group. The STD incidence rate was 8% (gonorrhea [9], chlamydia [7] and syphilis [20]) and was higher among younger than older individuals (11% younger vs. 7% middle-aged vs. 3% older) (p=0.02). Our results demonstrated that reported sexual activity decreases with advancing age but did not improve consistency of condom use. Regardless of age, STDs continue to be identified and this finding reinforces the need for secondary prevention efforts among all individuals living with HIV/AIDS.